Penggunaan Teknologi Hologram Dalam Novel Komet Minor Karya Tere Liye - Izanatul Baroroh; Dwi Ragil Wiyaningrum; Eva Dwi Kurniawan (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
Hologram technology in its development can provide information and views which contain three-dimensional objects (3D). Hologram technology is often found in literary works. This study aims to determine the description of the use of hologram technology in the Minor Komet novel by Tere Liye. The method used in this study is to use the hermeneutics approach, which is to provide descriptive to the text. Based on the results of the analysis and discussion found several hologram technology contained in the novel, including 1. advertising media, 2. gadgets found in the description directly or in dialogue between characters.